Rancang Bangun dan Evaluasi User Experience Sistem Short Link UNCP Menggunakan Metode System Usability Scale (SUS) - Wisnu Kurniadi; Risna Sari; Erwin Sukma (Infotek: Jurnal Informatika dan Teknologi, 2026)
Managing long URLs in higher education environments often poses challenges for efficient academic information dissemination. Universitas Cokroaminoto Palopo (UNCP) faces similar challenges, particularly in distributing links to academic information systems, research portals, and the Learning Management System (LMS). This study aims to design, develop, and evaluate an institution-based short link system deployed under the institutional subdomain short.uncp.ac.id, representing a distinctive institutional advantage over third-party services. The system was developed using the Agile Development methodology, adopting a three-tier architecture consisting of a React 18 and TypeScript-based presentation layer, a business logic layer handling URL validation and base-62 short code generation, and a data layer equipped with security mechanisms including link verification and institutional security badges. Core features include URL shortening, custom alias generation, QR Code generation, and a real-time analytics dashboard that processes click data in near real-time with visualizations of daily trends, user geographic distribution, and per-link engagement metrics. Usability evaluation was conducted using the System Usability Scale (SUS) method on 30 respondents from the UNCP academic community. The SUS instrument comprises 10 statements rated on a 1–5 Likert scale. Results indicate that the system achieved an average SUS score of 84.33, categorized as Excellent and graded B according to Bangor et al. (2009). These findings indicate that the UNCP short link system has a high level of usability and can be widely implemented across the campus environment. This study contributes to the development of an independent, secure, scalable, and institutionally branded academic digital infrastructure.